EFFECTIVENESS INDICATORS OF THE COMPETITIVE STAFF TRAINING SYSTEM IN HIGHER EDUCATIONAL INSTITUTIONS (International journal of artificial intelligence, 2024)
In this article, the demand for training competitive personnel with higher education in developed countries is considered to be quantitative, competitive and competitive environment, the effectiveness of scientific research and the acquisition of new knowledge, a radical increase in the quality of personnel training, the rapid introduction of advanced innovations into practice, and the transformation of modern knowledge into the main factor of economic growth are the most important tasks of all developed and developing countries today. The UN Sustainable Development Goals for 2030 also set a pressing task of “implementing mechanisms for improving the management of the education system, the process and tools for assessing the quality of education”[1]. According to the World Bank, “human capital” accounts for 64 percent of the world’s national wealth. This figure is 70 percent in high-income countries that are members of the Organization for Economic Cooperation and Development (OECD), 58 percent in upper-middle-income countries, and 41 percent in low-income countries”[2]. The impact of higher education on the development of the national economy, including regional development, is becoming a leading factor in innovative development.The scientific literature on the formation of performance indicators for construction organizations is reviewed. To assess and determine the economic efficiency of construction production, differentiated and general indicators of efficiency are used. The efficiency of using costs and resources of a certain type is expressed in differentiated indicators of efficiency: reflected in such indicators as volume indicators, final indicators and social results. Scientific and practical proposals for solving problems in the construction complex have been developed.